Surviving your social work placement - Lomax, Robert (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmi llan, 2010)
"This book is an essential study aid for social work students prepar ing for and undertaking work placements. Focussing on reflective practi ce and full of tips, quotes, activities and illustrations, it offers cl ear down-to-earth advice and support on how to get the most out of work -based learning opportunities"--
Introduction -- Getting started -- Learning in practice -- Using the ory and knowledge in practice -- Keeping service users central to your learning and practice -- Making the most of supervision --Being assesse d -- Managing stress on placement -- Troubleshooting -- Moving on from your placement -- Appendix A National occupational standards for social work (England, Wales and Northern Ireland) -- Appendix B. Standards in social work education (Scotland).
Includes bibliographical references (p. 139-141) and index.
Keywords: Social workers; Social service; Social service -- Vocational guidance